Advancements and challenges in triple-negative breast cancer: a comprehensive review of therapeutic and diagnostic strategies - Xiong, Nating; Wu, Heming; Yu, Zhikang (Frontiers in Oncology, 2024)
Triple-negative breast cancer (TNBC) poses significant challenges in oncology due to its aggressive nature, limited treatment options, and poorer prognosis compared to other breast cancer subtypes. This comprehensive review examines the therapeutic and diagnostic landscape of TNBC, highlighting current strategies, emerging therapies, and future directions. Targeted therapies, including PARP inhibitors, immune checkpoint inhibitors, and EGFR inhibitors, hold promise for personalized treatment approaches.Challenges in identifying novel targets, exploring combination therapies, and developing predictive biomarkers must be addressed to optimize targeted therapy in TNBC.Immunotherapy represents a transformative approach in TNBC treatment, yet challenges in biomarker identification, combination strategies, and overcoming resistance persist.Precision medicine approaches offer opportunities for tailored treatment based on tumor biology, but integration of multi-omics data and clinical implementation present challenges requiring innovative solutions. Despite these challenges, ongoing research efforts and collaborative initiatives offer hope for improving outcomes and advancing treatment strategies in TNBC. By addressing the complexities of TNBC biology and developing effective therapeutic approaches, personalized treatments can be realized, ultimately enhancing the lives of TNBC patients. Continued research, clinical trials, and interdisciplinary collaborations are essential for realizing this vision and making meaningful progress in TNBC management.